Population dynamics and stock assessment of Cirrhinus mrigala (Hamilton) in the Kaptai Reservoir, Bangladesh - Ahmed, K K U; Amin, S M N; Haldar, G C; Mazid, M A (Indian Journal of Fisheries, 2011)
Population dynamics and stock assessment of Cirrhinus mrigala in Kaptai Lake of Bangladesh was studied using the length-frequency based analysis of FiSAT software in order to evaluate the growth parameters, mortality rates, exploitation rates, maximum sustainable yield (MSY) and corresponding fishing mortality at this level. The study reveals that the fishes are harvested at a lower level than the optimum fishing mortality. This fishing pressure should be reduced to near 1.02 from the present average level of mortality, 1.21/yr to obtain MSY of 31.49 tons